Self-determined Motivation, Satisfaction with Life and Social integration of Adapted Sports Athletes in Athletics - Ferreira, Denise (2019)
Submitted by Marco Alexandre Silva Batista (marco.batista@ipcb.pt) on 2019-02-16T11:19:33Z No. of bitstreams: 1 Motivação-Autodeterminada-Satisfação-com-a-Vida-e-Integração-Social-de.pdf: 554561 bytes, checksum: 70efa4d0153be68363e36a8608095006 (MD5)